The last million : Europe's displaced persons from World War to Cold War - Nasaw, David 1945- (Penguin Press, 2020)
From Poland: Forced Laborers, 1941-45 -- From Latvia, Lithuania, Estonia, and Western Ukraine -- From the Concentration and Death Camps -- Alone, Abandoned, Determined, the She'erit Hapletah Organizes -- The Harrison Mission, Report, and Consequences -- The U.S., the UK, the USSR, and UNRRA -- Inside the DP Camps -- "The War Department Is Very Anxious" -- "U.S. Begins Purge in German Camps. Will Weed Out Nazis, -- Fascist Sympathizers and Criminals Among Displaced Persons," -- New York Times, March 10, 1946 -- The Anglo-American Committee of Inquiry Issues Its Report -- The Polish Jews Escape into Germany -- Fiorello La Guardia to the Rescue -- The Death of UNRRA -- "Send Them Here," Life Magazine, September 23, 1946 -- Fact-Finding in Europe -- "The Best Migrant Types" -- "So Difficult of Solution" Jewish Displaced Persons -- "Jewish Immigration Is the Central Issue in Palestine Today" -- "A Noxious Mess Which Defies Digestion" -- "A Shameful Victory for [the] School of Bigotry" -- "Get These People Moving" -- "The Utilization of Refugees from the Soviet Union -- in the U.S. National Interest" -- The Displaced Persons Act of 1950 -- McCarran's Internal Security Act Restricts the Entry of Communist Subversives -- "The Nazis Come In" -- The Gates Open Wide -- Aftermaths.